XPS binding energy shifts as a function of bond distances: a case study of CO. (13th April 2022) - Bagus, Paul S; Sousa, Carmen; Illas, Francesc
Abstract: The O(1s) and C(1s) XPS core-level binding energies. BEs, have been studied as a function of the C–O internuclear distance for a large range of distances. The BE( r ) for both BEs show considerable variation over the distances studied which is, however, different for the O(1s) and C(1s) BEs. The origin of the dependence on C–O distance is established and shown to involve more than the electric field generated because of the charge separation within CO being C + q and O − q . Furthermore, the BE( r ) is shown to be different for Hartree–Fock and correlated wavefunctions indicating that the BE( r ) can provide evidence of how electron correlation modifies the valence charge distribution. The difference between the O(1s) and C(1s) BEs is examined and it is proposed that this difference can be used as a measure of the accuracy of theoretically predicted BEs. It is believed that the features found for CO may be representative for the BE variations with geometry for other systems; an effect that has been mostly overlooked.